Open-RAN: Changing Landscape of Competition under Bi-polarization of Telecommunications Policy? - Benyathip Laorrojwong; Natchaya Makarathat (International Telecommunications Society (ITS), 2024)
The Open RAN model has recently been put to the forefront of debate on how the open networking technologies would benefit the telecom operator, vendors and tech sectors in terms of competition, freedom, and openness. The Open RAN has introduced an open interface which allows telecom operators to choose their own combinations of hardware and software. In other words, Open RAN might be replacing the traditional/old model, which offers bundle hardware and software, already integrated , in a monolithic architecture. The traditional 5G tech architect uses proprietary equipment to connect devices to the network. This means all parts (hardware and software) of 5G network are manufactured by the same company. While this architecture guarant ees compatibility and operability of the network, it also leads to the conduct of monopolies in the market as well as technology dependency. The new invention of Open RAN model, in contrast, supports the disaggregation of hardware and software. In the simple terms, the operating system will come from Company A, antennas and cells will come from Company B, and a microchip will be used from Company C. This type of network architecture is designed to reduce the risk of dependencies and disrupt the nature of 5G monopolistic market. The initial purpose of the Open RAN, in this sense, is aimed at developing 5G network technology by using open interfaces, allowing operators to be able to use equipment from different manufacture. From the economics perspective, Open RAN model promotes competition and innovations, avoids the formation of tech oligopolies, diversifies suppliers and mitigates risks, and importantly leads to a decoupling of bi-polarization of the U.S. and Chinese technology.
Keywords: 330; Open-RAN; Economics; Competition; Geopolitics; Bi-polarization; Conflicts; Technology policy